(3eSGdc GdCagGe Edi JfbjM TQGFY GdESdGes - (3GdLhGO GdHZOGOj , LhGO Hf SYO (B((3Ch SYjO(B) (3Hf LhGO GdHZOGOj GdcGXej, GdLhGO GdHZOGOj,J (B1065 (3g` s ((3eMeO Hf EHQGgje GdMfai s)
(3ChdgG (B:s
(3cJGH GdfcGM GdfcGM jSJYed dZI ai GdhW cKjQkG s
(3BNQgG (B:s
(3heG PcQ ef GdNHGQ CLhO ef GdfSN s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B142 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B165s
Keywords: (3abg GdePGgH GdCNQis